A Simple Method for Finding Shadow Prices Using Leontief Matrices - Sakellariou, Dimitri M. (The Review of Economics and Statistics, 1981)
faces, however elastic it may be. But it is necessary to look beyond the elasticity of the curve to determine whether or not this is the case. Or consider two demand estimation situations, identical in terms of the supply elasticities involved. Differences in the variability of supply could make for large differences in the quality and appropriateness of OLS estimates. Yet a researcher relying on elasticity would be totally unaware of the differences in OLS bias in the two situations. Finally, concern about elasticities turns attention from the central question in choosing an estimator in the face of possible OLS bias: the relative shifting in the equations involved. That this is an important factor is well known, having been pointed out by Working as long ago as 1927, and by many others since. However, this essential factor is often overlooked in empirical situations.